2013
DOI: 10.4137/bcbcr.s10701
|View full text |Cite
|
Sign up to set email alerts
|

ER, PR, HER2, Ki-67 and CK5 in Early and Late Relapsing Breast Cancer—Reduced CK5 Expression in Metastases

Abstract: Breast cancer can recur even decades after the primary therapy. Markers are needed to predict cancer progression and the risk of late recurrence. The estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor-2 (HER2), proliferation marker Ki-67, and cytokeratin CK5 were studied to find out whether their expression or occurrence in subgroups of breast cancers correlated with the time of recurrence. The expression of HER2, ER, PR, Ki-67, and CK5 was studied by IHC in 72 primary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 46 publications
(79 reference statements)
5
57
2
2
Order By: Relevance
“…Seventy-nine percent of new cases and Eighty -Eight percent of death due to breast cancer happened in 50 years old women and older. Reduction of the incidence rate in eighty years old women and older, is probably due to the decrease in the rate of screening [35]. Data analysis in present study indicates no correlation between the methylation of MAP9 gene and age of patients in breast cancer samples (P>0.05).…”
Section: Age Of Patientsmentioning
confidence: 45%
“…Seventy-nine percent of new cases and Eighty -Eight percent of death due to breast cancer happened in 50 years old women and older. Reduction of the incidence rate in eighty years old women and older, is probably due to the decrease in the rate of screening [35]. Data analysis in present study indicates no correlation between the methylation of MAP9 gene and age of patients in breast cancer samples (P>0.05).…”
Section: Age Of Patientsmentioning
confidence: 45%
“…Em estudo realizado com 228 pacientes diagnosticadas com câncer de mama TN, um terço apresentou doença metastática 19 , valor menor do que o encontrado em nosso estudo (52%). O risco de recidiva foi fortemente associado ao câncer de mama TN, colaborando para predizer seu pior prognóstico 20 . Comumente as metástases em paciente com carcinomas mamários ocorrem no cérebro (15%), nos pulmões (14%), nos Martins LC, Rezende RMD, Cordeiro JABL, Paula HSC, Bastos DR, Vilanova-Costa CAST, Saddi VA, Silva AMTC ossos (11%), no fígado (8%), e cerca de 14% das pacientes apresentam recidiva loco-regional 19 .…”
Section: Discussionunclassified
“…Em estudo realizado com pacientes do Hospital Universitário de Saint Vicent (Irlanda), foram comparados tecidos mamários de pacientes com câncer de mama primário e com câncer de mama metastático, além de tecido mamá-rio sem doença, e os resultados apontaram uma expressão de EpCAM mais significativa em câncer de mama primário e em linfonodos contendo doença metastática do que em tecido mamário sadio 24,25 . 20,21 . Em nosso trabalho, o tamanho do tumor inicial se mostrou como um fator relevante e responsável pela recorrência do câncer (p=0,0497).…”
Section: Discussionunclassified
“…It reflects the tumor origin, but does not change with the tumor development [19]. Kristiina et al [20] have detected 72 cases of primary breast cancer and found that, the positive rate of CK5/6 expression is 31%, but it in secondary breast cancer is only 11%. Results of this study showed that, the positive rate of Her-2 protein expression in non-comedo type group was significantly lower than that in comedo type group (P<0.05), with no significant difference of positive rate of CK5/6 protein expression between two groups (P>0.05).…”
Section: Discussionmentioning
confidence: 99%